2011
DOI: 10.1021/ja2015586
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Pd-Catalyzed sp3 C−H Olefination: A Route to Both N-Heterocyclic Scaffolds and Alkenes

Abstract: This communication describes a new method for the Pd/polyoxometalate-catalyzed aerobic olefination of unactivated sp3 C–H bonds. Nitrogen heterocycles serve as directing groups, and air is used as the terminal oxidant. The products undergo reversible intramolecular Michael addition, which protects the mono-alkenylated product from over-functionalization. Hydrogenation of the Michael adducts provides access to bicyclic nitrogen-containing scaffolds that are prevalent in alkaloid natural products. Additionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(100 citation statements)
references
References 32 publications
0
95
0
2
Order By: Relevance
“…However, the oxidative alkenylation of heteroarenes is named the Moritani-Fujiwara reaction. [8,9] In this regard, different palladium [10][11][12][13] and rhodium catalysts [14][15][16] have already been used to promote the oxidative alkenylation of heteroarenes with a variety of directing groups, namely, imines, [17,18] amines, [19] and carboxylates. [20,21] Rutheniumcatalyst-directed arylation of unactivated C-H bonds with phenols was reported by Ackermann.…”
Section: Introductionmentioning
confidence: 99%
“…However, the oxidative alkenylation of heteroarenes is named the Moritani-Fujiwara reaction. [8,9] In this regard, different palladium [10][11][12][13] and rhodium catalysts [14][15][16] have already been used to promote the oxidative alkenylation of heteroarenes with a variety of directing groups, namely, imines, [17,18] amines, [19] and carboxylates. [20,21] Rutheniumcatalyst-directed arylation of unactivated C-H bonds with phenols was reported by Ackermann.…”
Section: Introductionmentioning
confidence: 99%
“…[52] In nachfolgenden Beiträgen wurden mehrere palladiumkatalysierte dehydrierende Cyclisierungen entwickelt, um Stickstoffheterocyclen zu synthetisieren (Schema 31). [53] Die…”
Section: Methodsunclassified
“…The authors of this report found that the addition of pivalic acid (PivOH) promoted the C-H bond activation process. Although several reports were available at the time describing the activation of the C(sp 3 )-H bonds of methyl groups for the synthesis of cyclobutene 62) and five membered rings, [63][64][65][66][67][68] there were no reports pertaining to Pd-catalyzed C(sp 3 )-H activation followed by a C-C bond forming reaction to give a methylene or methine moiety. For this reason, several groups became interested in the development of C(sp 3 )-H functionalization chemistries.…”
Section: )-H Functionalization As a Strategy For The Synthesis Of Oximentioning
confidence: 99%